2016
DOI: 10.46743/2160-3715/2016.2149
|View full text |Cite
|
Sign up to set email alerts
|

Aggressive Humor as a Negative Relational Maintenance Behavior during Times of Conflict

Abstract: This study explores how aggressive humor is used as a negative relational maintenance behavior during conflicts in romantic relationships. Negative relational maintenance behaviors are questionable interpersonal behaviors romantic partners use to relieve personal tensions about the state of the relationship while still keeping the relationship in existence. Twenty-six participants in committed romantic relationships participated in seven semi-structured group interviews, and transcripts from these group interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…In this study, it was seen that the most used humor style by the patients was the affiliative humor style, and the patients used compatible-positive (affiliative and self-enhancing) humor styles more than incompatible-negative (aggressive and selfdefeating) humor styles. Studies have shown that patients use affiliative humor more [8,22]. It is stated that individuals who have compatible-positive humor styles, which include affiliative humor and selfenhancing humor styles, use humor in an accepting way to contribute to themselves and others in order to contribute to their relations with others and improve their social relations in a tolerant and harmless way [9,12].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In this study, it was seen that the most used humor style by the patients was the affiliative humor style, and the patients used compatible-positive (affiliative and self-enhancing) humor styles more than incompatible-negative (aggressive and selfdefeating) humor styles. Studies have shown that patients use affiliative humor more [8,22]. It is stated that individuals who have compatible-positive humor styles, which include affiliative humor and selfenhancing humor styles, use humor in an accepting way to contribute to themselves and others in order to contribute to their relations with others and improve their social relations in a tolerant and harmless way [9,12].…”
Section: Discussionmentioning
confidence: 99%
“…The scale, which consists of 25 items, is a five-point Likert type. While 17 items of the Death Anxiety Scale have a positive sentence structure (1,2,3,5,6,7,8,9,12,14,15,16,18,19,20,22, 24 th items) the other 8 items have a negative sentence structure (items 4, 10, 11, 13, 17, 21, 23, 25 th items). For the scale to determine the death anxiety level, the lowest 0 and the highest 100 points can be obtained, and a high score indicates a high level of anxiety.…”
Section: Thorson-powell Death Anxiety Scale (Tpdas)mentioning
confidence: 99%
See 3 more Smart Citations